ANALISIS KUALITAS LAYANAN JARINGAN TELKOMSEL KABUPATEN LEMBATA - Johanis F. M. Bowakh; Beby H. A. Manafe (Jurnal Media Elektro, 2020)
The services of Telkomsel celullar have not evenly spread throughout the entire region of Lembata Regency. Furthermore the quality of the coverage area of the service that has not maximized results in frequent failed calls or disconnected communications. This research aims to determine location of signal ditribution and quality in each Telkomsel BTS in order to improve and expand the quality of service. This measurement used the drive test method with the G-Net Track application to measure receive signal level (Rxlev). The drive test based on four directions of each BTS with 3 km distance in each direction. The result then analyzed and mapped with Google Earth. The result is not absolute because the antenna sensitivity of the receiver signal varies based on the type of handphone. The result of 800 measurement points for RxLev in Lembata county region show that 327 points or 40.875% is very good category, 170 points or 21.25% is good category, 147 point or 18.375% is medium category, 110 point or 13.75% is bad category, and 46 point or 5.75% is very bad category. It is only ± 36,98% of the total area of Lembata Regency has coverage by Telkomsel services.